Rural and Urban Differences in the Commission of Animal Cruelty - Tallichet, Suzanne E. (International journal of offender therapy and comparative criminology, 2005)
Despite the recent surge in society's interest in human violence, relatively few studies have been conducted examining the closely related phenomenon of animal cruelty. Although several researchers have begun to identify some of the correlates of animal cruelty, few have attempted to understand how differences in the backgrounds of rural and urban residents have led to their abuse of animals. Using survey data from261 inmates, the authors investigate how demographic, familial differences and species type have contributed to the frequency of acts of animal cruelty. In general, early exposure to animal abuse is a strong predictor of the subsequent behavior. However, rural inmates learned to be cruel by watching family members exclusively, whereas urban inmates learned from family members and friends. Moreover, urban inmates chose dogs, cats, and wild animals as their target animals; however, rural inmates chose only cats